RETRACTED: Environmental expertise and its importance for ensuring natural resource security - Azarkhin Aleksey; Abduev Sayhan (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001